The challenges of New Regionalism: Towards modern community and territory - Miszczak, Katarzyna (Wyzwania nowego regionalizmu: w kierunku współczesnego społeczeństwa i terytorium, 2014)
The paper contains ascertainments that changes taking place in the structure of modern territory and transformations in modern society are/or will be still determined by the processes of transfer of technologies and innovations, diffusion of creativity and differential development of civilizations. Indigenization of globalization (which the author interprets as glocalization) represents a shift from a more territorialized learning process bound up with the nation-state society to one more fluid and translocal. New Regionalism as a paradigm for regional development emphasizes smart, inclusive and sustainable economies. In particular, the author presents a framework for analysing New Regionalism which should include determinants such as innovative capacity, creativity, networks, high level of social capital and the role of civilization in developing regional economic resilience
Biblioteka Regionalisty, 2014, Nr 14, s. 59-74
Keywords: creativity; social capital; networks; innovations; civilization; kreatywność; kapitał społeczny; sieci; innowacje; cywilizacja